Mediação do pensamento computacional e programação no processo de interação das crianças na educação infantil - Bremm, Cristiane Inês (2018)
This research was developed in the Professional Master of the Postgraduate Program in Educational Technologies in Network, in the research line of Management of Educational Technologies in Network. By investigating how the mediation of computational thinking activities and programming can contribute to the interaction in early childhood education, a pedagogical proposal was developed whit two didactic sequences, that constituted the product of this research: one teaching-learning computational thinking unplugged, without the technologies, and one of teaching-learning computacional thinking plugged, mediated by digital technologies, specifically the ScratchJr software. As specific objectives we propose: a) to construct a didactic-methodological proposal (product), based on computational thinking and programming (ScratchJr software), for teaching-learning processes in children's education, preferably on mobile devices; b) implement a teaching-learning process in children's education guided by active research on the potential of computational thinking and programming for the interaction process; c) evaluate if the activities of computational thinking and programming contribute to interaction in early childhood education. From this perspective, it was adopted as approach the educational research-action, in which data were collected through observations, visual data and field diary. As main results we highlight the role of the teacher as mediator of student knowledge, in which he is an active subject and both teach and learn together. Interaction was present throughout the action-research process, and was enhanced by technologies, establishing a dialogic, problematizing and collaborative perspective between teachers and students. This process also contributed to the professional and technological formation of those involved.